Guidance and Counseling Teacher Skills in Developing Guidance and Counseling Management in Schools - Siti Fauziah; Neviyarni S; Yarmis Sukur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Guidance and counseling teachers have an equal role in interests with subject teachers, both function in a complementary and closely related manner. The existence of guidance and counseling teachers/counselors is regulated in the National Education System Law (SPN) Chapter I Article 1 Paragraph 6. As educators, guidance and counseling teachers must also master 4 competencies according to Peremndiknas No.26 of 2009. So, by knowing this, guidance and counseling teachers can provide guidance and counseling services according to their duties, roles and responsibilities. After that, it can produce effective and efficient guidance and counseling management for schools and students. The purpose of this study was to determine the skills of guidance and counseling teachers in developing guidance and counseling management in schools. The method chosen was literature study. Literature study involves collecting data, reading and recording information, and managing research materials. The results of this study are that guidance and counseling has significant main tasks and functions in the implementation of education programs. In guidance and counseling services, BK teachers should carry out the duties, roles and responsibilities that have been determined based on the Law that has been stated.